A simple route to tetracyclic oxazepine-fused pyrroles via metal-free [3+2] annulation between dibenzo[b, f][1, 4]oxazepines and aqueous succinaldehyde. (12th December 2018) - Choudhary, Sachin; Singh, Anoop; Yadav, Jyothi; Mir, Nisar A.; Anthal, Sumati; Kant, Rajni; Kumar, Indresh
Abstract : A direct method for the synthesis of tetracyclic oxazepine-fused pyrroles has been developed through [3+2] annulation between aqueous succinaldehyde and dibenzo[ b, f ][1, 4]oxazepines under metal-free conditions. Abstract : A direct method for the synthesis of new tetracyclic oxazepine-fused pyrroles has been developed through [3+2] annulation between aqueous succinaldehyde and dibenzo[ b, f ][1, 4]-oxazepines under metal-free conditions. This one-pot synthetic protocol involves proline-catalyzed direct Mannich/cyclization between aqueous succinaldehyde and seven-membered oxazepine-imines, followed by an IBX-mediated oxidation sequence with high yields (up to 90%).